2021
DOI: 10.1111/jcmm.16919
|View full text |Cite
|
Sign up to set email alerts
|

Telocytes in the human ascending aorta: Characterization and exosome‐related KLF‐4/VEGF‐A expression

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Recently, we showed that telocytes are involved in HTA, and the number of telocytes was positively correlated with increases in chronic disease and aortic diameter in TAA samples [ 45 , 46 ]. An increase in the number of TCs seems to be positively related to chronic hypoxia and/or cellular stress of the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that telocytes are involved in HTA, and the number of telocytes was positively correlated with increases in chronic disease and aortic diameter in TAA samples [ 45 , 46 ]. An increase in the number of TCs seems to be positively related to chronic hypoxia and/or cellular stress of the tissue.…”
Section: Resultsmentioning
confidence: 99%
“…TCs could promote angiogenesis [ 37 ]. Aschacher et al describe these cells in blood vessels and hypothesise that they might be involved in aortic tissue homeostasis by shedding microvesicles (sMVs) and exosomes containing angiogenic factors, such as VEGF—A [ 38 ]. Our results show that a declining number of myometrial and oviductal TCs in patients with uterine myoma correlates with a low expression of VEGF in the same samples of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…(Heo et al, 2020) PDGF-A The change of extracellular matrix composition was simulated by PDGF-A, which is important for the formation of aortic aneurysms through the induction of pathological phenotype switching of SMCs. (Aschacher et al, 2021) PDGF-AA Exosomes including PDGF-AA derived from differentiating human skeletal myoblasts (HSkM) can induce in vitro myogenesis of human adipose-derived stem cells (HASCs) and improves in vivo muscle regeneration. (Choi et al, 2016) PDGF-AA,PDGF-BB…”
Section: Parkinson's Disease Treatment Based On Single-cell Transcrip...mentioning
confidence: 99%